Forgotten Double-J Stent – An Extra Burden to both Patient and Urosurgeon: A Single Center Experience - Shrestha, Naresh Man (Journal of Nepalgunj Medical College, 2021)
Introduction: Double-J stent is widely used in urological as well in few non urological operations, which must be removed or replace timely. Otherwise unnecessary complications can be encountered. Forgotten Double-J stent is one of them.Aims: To find out the cause of forgotten Double-J stent, its complications and prevention.Methods: It is a hospital based study done from 2017-2020 in Nepalgunj Medical College. 33 patients fulfilling the inclusion criteria were included and reviewed for the cause, complications and management of forgotten Double-J stent.Results: Out of 33 patients, 25 (75.75 %) were operated at Nepalgunj Medical College and 8(24.24%) were in other hospitals. Among them, major causes of forgotten Double- J stent were found due to Poor financial condition and ignorance 10(30.30%) and remote inhabitant 10(30.30%). Major symptoms were flank painalone in 10(30.30 %) and recurrent fever with flank pain with positive urine culture in 8(24.24%). 21 patients (63.63%) required additional surgical treatment such as percutaneous nephrolithotripsy, ureterorenoscopic lithotripsy, percutaneous cystolithotripsy, perurethtalcystolithotripsy, open cystolithotomy.Conclusion: Forgotten Double-J stent is one of the major complications if not removed timely which may increases morbidity, mortality and financial burden. The rate of it may minimize if patients are made aware for the complications of Double-J stent and maintain stent registry properly.